Burden of Disease Associated with Alcohol Use Disorders in the United States. (15th January 2014) - Rehm, Jürgen; Dawson, Deborah; Frick, Ulrich; Gmel, Gerrit; Roerecke, Michael; Shield, Kevin D.; Grant, Bridget
<x xml:space="preserve">Abstract</x> Background Alcohol use disorders (AUD) have long been considered to be some of the most disabling mental disorders; however, empirical data on the burden of disease associated with AUD have been sparse. The objective of this article is to quantify the burden of disease (in disability‐adjusted life years [DALYs] lost), deaths, years of life lost due to premature mortality (YLL), and years of life lost due to disability (YLD) associated with AUD for the United States in 2005. Methods Statistical modeling was based on epidemiological indicators derived from the National Epidemiologic Survey on Alcohol and Related Conditions. Formal consistency analyses were applied. Risk relations were taken from recent meta‐analyses and the disability weights from the burden of disease study of the National Institutes of Health. Monte Carlo simulations were used to derive confidence intervals. All analyses were performed by sex and age. Sensitivity analyses were undertaken on key indicators. Results In the United States in 2005, 65, 000 deaths, 1, 152, 000 YLL, 2, 443, 000 YLD, and 3, 595, 000 DALYs were associated with AUD. For individuals 18 years of age and older, AUD were associated with 3% of all deaths (5% for men and 1% for women), and 5% of all YLL (7% for men and 2% for women). The majority of the burden of disease associated with AUD stemmed from YLD, which accounted for 68% of DALYs associated with AUD (66% for men and 74% for women). The youngest age group had the largest proportion of DALYs associated with AUD stemming from YLD. Conclusions Using data from a large representative survey (checked for consistency) and by combining these data with the best available evidence, we found that AUD were associated with a larger burden of disease than previously estimated. To reduce this disease burden, implementation of prevention interventions and expansion of treatment are necessary.